Alphaworld: two snakes - Wignell, Edel (Horwitz Education London, 2003)
"Two Snakes" could be a captivating story about the contrasting lives of two snake characters, perhaps representing different traits or philosophies. One snake might be bold and adventurous, while the other is cautious and wise.